Standing and Supine Hamstring Stretching Are Equally Effective - Decoster, Laura C (National Athletic Trainers Association, 2004)
Objective: To evaluate the relative effectiveness of standing and supine hamstring stretching in increasing hamstring flexibility as measured by increasing range of motion at the knee. Design and Setting: The trial was randomized, and the setting was local academic physical therapy and physical therapist assistant programs. Subjects: Twenty-nine healthy subjects who exhibited limited hamstring muscle flexibility bilaterally (22 women, 7 men, 25.9 ± 6.13 years of age) volunteered to participate in this study. Subjects were randomly assigned a different stretch for each leg. Each leg was stretched 3 days per week for 3 weeks (3 × 30 seconds). Stretching sessions were supervised. Measurements: We measured supine active knee extension. Measurements were taken before and after the 3-week stretching phase by the same investigator, who was blind to limb assignment. We calculated a 2-way mixed-design analysis of variance and Tukey Honestly Significant Difference post hoc tests to analyze data. An independent t test was performed to determine whether the change scores in the stretching groups differed by sex. Results: Prestretching and poststretching measurements were significantly different for both the standing and supine stretch (<0.05). No significant difference (P > .05) in change score existed between the 2 stretches or between the sexes. Conclusions: The standing and supine hamstring stretches were comparably effective in improving flexibility.